Compensated Hydroxyl Radical Protein Footprinting Measures Buffer and Excipient Effects on Conformation and Aggregation in an Adalimumab Biosimilar - Misra, Sandeep K. (AAPS J, 2019)
Unlike small molecule drugs, therapeutic proteins must maintain the proper higher order structure (HOS) in order to maintain safety and efficacy. Due to the sensitivity of many protein systems, even small changes due to differences in protein expression or formulation can alter HOS. Previous work has demonstrated how hydroxyl radical protein footprinting (HRPF) can sensitively detect changes in protein HOS by measuring the average topography of the protein monomers, as well as identify specific regions of the therapeutic protein impacted by the conformational changes. However, HRPF is very sensitive to the radical scavenging capacity of the buffer; addition of organic buffers and/or excipients can dramatically alter the HRPF footprint without affecting protein HOS. By compensating for the radical scavenging effects of different adalimumab biosimilar formulations using real-time adenine dosimetry, we identify that sodium citrate buffer causes a modest decrease in average solvent accessibility compared to sodium phosphate buffer at the same pH. We find that the addition of polysorbate-80 does not alter the conformation of the biosimilar in either buffer, but it does provide substantial protection from protein conformational perturbation during short periods of exposure to high temperature. Compensated HRPF measurements are validated and contextualized by dynamic light scattering (DLS), which suggests that changes in adalimumab biosimilar aggregation is a major driver in measured changes in protein topography. Overall, compensated HRPF accurately measured conformational changes in adalimumab biosimilar that occurred during formulation changes, and identified the effect of formulation changes on protection of HOS from temperature extremes.